2022
DOI: 10.3390/pathogens11040435
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Case Series of Thrombotic Deaths in Patients over 50 with Comorbidities Temporally after modRNA COVID-19 Vaccination

Abstract: Coronavirus disease 2019 (COVID-19) is the most dramatic pandemic of the new millennium; to counteract it, specific vaccines have been launched in record time under emergency use authorization or conditional marketing authorization by virtue of a favorable risk/benefit balance. Among the various technological platforms, there is that exploiting a nucleoside-modified messenger RNA (modRNA), such as Comirnaty®, and that which is adenoviral vector-based. In the ongoing pharmacovigilance, the product information o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…As a possible mechanism for thromboembolic events, massive platelet activation through platelet factor 4 has been proposed [ 30 ]. Prior studies have also reported thrombotic events after the onset of respiratory symptoms, which is consistent with cluster 3, which consisted primarily of patients ≥ 65 years (29.6% of cluster 3) [ 28 , 29 ]. Thus, physicians need to monitor patients who complain of respiratory symptoms for the possibility of further thrombotic events.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…As a possible mechanism for thromboembolic events, massive platelet activation through platelet factor 4 has been proposed [ 30 ]. Prior studies have also reported thrombotic events after the onset of respiratory symptoms, which is consistent with cluster 3, which consisted primarily of patients ≥ 65 years (29.6% of cluster 3) [ 28 , 29 ]. Thus, physicians need to monitor patients who complain of respiratory symptoms for the possibility of further thrombotic events.…”
Section: Discussionsupporting
confidence: 70%
“…Therefore, we labeled cluster 3 as “respiratory/thrombotic AEs.” Moreover, cluster 3 showed a high proportion of vascular disorders, including pulmonary embolism, deep vein thrombosis, and thrombosis, along with respiratory disorders. Previous case reports have reported thrombotic death immediately after the onset of symptoms of dyspnea [ 28 ] and deep vein thrombosis [ 29 ] following administration of mRNA COVID-19 vaccines. As a possible mechanism for thromboembolic events, massive platelet activation through platelet factor 4 has been proposed [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scientific proof of the possible complications, even fatal, in young people due to COVID-19 vaccination lies in vaccine-induced immune thrombotic thrombocytopenia (VITT), a new blood clotting syndrome initially described in association with adenovirus vector-based COVID-19 vaccines [ 22 , 23 , 24 ]. VITT is characterized by both arterial and venous thrombotic events in unusual sites, such as splanchnic veins and cerebral venous sinus, accompanied by low platelets count (<150 × 10 3 /mm 3 ), markedly elevated D-dimer (>4 times upper limit of normal), and positive Platelet Factor 4 (PF4) Heparin-Induced Thrombocytopenia (HIT) Enzyme-Linked Immuno-Sorbent Assay (ELISA), 4–42 days after vaccine administration; pulmonary embolism and disseminated intravascular coagulation may also occur [ 25 ]. Among the lab tests available today for the detection of pathological platelet-activating antibodies against PF4, that is to say, VITT triggers, HIT ELISA is the one with the greatest validity and reliability and with the most appropriate sensitivity, reaching around 95% [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…VITT is characterized by both arterial and venous thrombotic events in unusual sites, such as splanchnic veins and cerebral venous sinus, accompanied by low platelets count (<150 × 10 3 /mm 3 ), markedly elevated D-dimer (>4 times upper limit of normal), and positive Platelet Factor 4 (PF4) Heparin-Induced Thrombocytopenia (HIT) Enzyme-Linked Immuno-Sorbent Assay (ELISA), 4–42 days after vaccine administration; pulmonary embolism and disseminated intravascular coagulation may also occur [ 25 ]. Among the lab tests available today for the detection of pathological platelet-activating antibodies against PF4, that is to say, VITT triggers, HIT ELISA is the one with the greatest validity and reliability and with the most appropriate sensitivity, reaching around 95% [ 25 ]. Although these adverse events are very rare, they exceeded what would be expected in the general population [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the few autopsy case reports that include histopathological analysis of HIT [30][31][32][33], the lung and gastrointestinal tract are reported as the main thrombosis sites in HIT. TTS/VITT, which is suspected to be associated with autoimmune HIT, develops 4 to 28 days after vaccination and causes thrombosis characteristically in atypical sites such as the cerebral venous sinus, hepatic vein, and splenic vein [34][35][36][37][38][39][40]. Although the thrombi in CAPS share an organ distribution similar to that of our case [41][42][43][44], thrombi in CAPS form regardless of the shear stress in arterioles and/or capillaries; thus, it might be difficult to explain our four characteristics findings.…”
Section: Discussionmentioning
confidence: 99%